Comparative analysis of performance of private and public healthcare systems in Nepal - Sah, Mukesh Kumar; Sangroula, Raj Kumar; Arul Kumar, S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Though government of every country has their own health delivery system, private sector in the delivery of health service is undeniable and same is true for Nepal. Private healthcare services in Nepal are making better efforts as compared to public health care services. The aim of the study was to compare the performance of private and public healthcare systems in Nepal. Methods: A hospital based cross sectional study was conducted in which five hospitals each from private and public healthcare systems were chosen purposively from five developmental regions of Nepal. The patients visiting the healthcare systems were randomly chosen for the study from the admission registers of the hospitals. This study was approved from the Annamalai University, Tamil Nadu (India). Before data collection, permission was taken from corresponding hospital administration and written consent was taken from respondents of the study. Bivariate analysis was performed to compare the performance of the private and public hospitals. Results: Most of the patients visiting the private hospitals were patients with higher education and income. Public hospitals were more accessible and transparent than the private hospital. Doctors’ punctuality and responsibility were higher in public healthcare systems. Overall patient satisfaction and quality of services provided were significantly higher in the private healthcare systems. Fairness, responsiveness and behavior of the health personnel were almost equally satisfactory in both public and private healthcare systems. Conclusions: The overall services quality and patient satisfaction is higher in private healthcare systems so Government of Nepal should focus on improving services quality, facilities of public healthcare systems so that patient can get easily accessible quality health services with better patient satisfaction.